Optimalisasi Pendataan Anak Serta Donatur Yayasan Kasih Mandiri Bersinar dengan Metode Prototype - Filomon Kiik Tahu; Winton Ginting; NM Faizah (Design Journal, 2024)
The Yayasan Kasih Mandiri Bersinar (YKMB) is a child welfare institution established in May 1996. However, data management for foster children and donors is still performed manually using notebooks or Microsoft Excel, leading to challenges such as data entry errors, difficulties in report generation, data loss, and limitations in information retrieval. This study employs a prototyping method to develop a web-based application using PHP and MySQL. The prototyping approach allows iterative testing and refinement of the application based on user feedback throughout the development process. The results indicate that the application meets the foundation’s requirements, enhances data management efficiency, and reduces the risks of errors and data loss. Additionally, the application facilitates faster and more structured report generation, supporting better data management practices at YKMB.